Squamous cell carcinoma of eye in buffaloes - A report of two cases - Hari Krishna, Nunna Veera Venkata; Sreenu, Makkena; Nagaraju, Narayanappa (Buffalo Bulletin, 2020)
The present report describes about squamous cell carcinoma of eye in two she buffaloes with pulmonary metastasis in one case. Wide margin excision with extirpation of the eye and application of liquid nitrogen resulted in successful outcome. No recurrence was observed for up to six months post-operatively.